2020
DOI: 10.1177/0954408920938614
|View full text |Cite
|
Sign up to set email alerts
|

Variation and artificial neural network prediction of profile areas during slant type taper profiling of triangle at different machining parameters on Hastelloy X by wire electric discharge machining

Abstract: In the present research work, an in-house developed fixture is used to achieve taper profiles which avoids the disadvantages in convention tapering operation in wire electric discharge machining like wire bend, inaccuracies in taper, insufficient flushing, guide wear etc. A simple triangular profile was machined at 0°, 15° and 30° slant/taper angles. These taper profile areas are investigated for various machining parameters like wire guide distance, corner dwell time, wire offset and cutting speed ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Soni et al [18] used the response surface method and ANN for the prediction of cutting speed in WEDM of shape memory alloys. Manoj and Narendranath [19,20] have used ANN for the prediction of profile areas and profiling speed. It was concluded that both machining parameters and taper angle influence the accuracy and profiling speed.…”
Section: Introductionmentioning
confidence: 99%
“…Soni et al [18] used the response surface method and ANN for the prediction of cutting speed in WEDM of shape memory alloys. Manoj and Narendranath [19,20] have used ANN for the prediction of profile areas and profiling speed. It was concluded that both machining parameters and taper angle influence the accuracy and profiling speed.…”
Section: Introductionmentioning
confidence: 99%
“…As the u parameter increases the profile area also increases with certain offset distance. 23,29 As u increases, the wire has to travel lager circumference compared to the programmed profile which increases the wire vibrations. 25,27,29 This leads to small variations in the increase as seen at 40mm for 0 , 15 and 30 of 1 mm taper profiles.…”
Section: Effect Of Machining Parameters On Circular Profile Areasmentioning
confidence: 99%
“…23,29 As u increases, the wire has to travel lager circumference compared to the programmed profile which increases the wire vibrations. 25,27,29 This leads to small variations in the increase as seen at 40mm for 0 , 15 and 30 of 1 mm taper profiles. With the increase in u parameter, the circular area also increases as shown in Figure 5 (a) this can be seen in all the taper angles.…”
Section: Effect Of Machining Parameters On Circular Profile Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…The supremacy of the brass electrode was established through effective discharge energy transfer. Manoj and Narenderanath [ 14 ] machined triangular profiles having 0°, 15°, and 30° taper angles to study inaccuracy at Hastelloy X (nickel alloy). They found that insufficient flushing attributed to the generation of wire vibrations which increased slant angle inaccuracies (taper error).…”
Section: Introductionmentioning
confidence: 99%